BIBLIOMETRIC ANALYSIS AND MAPPING OF GREEN BRANDING AND CONSUMPTION BEHAVIOR RESEARCH DEVELOPMENTS - Anwar, Dini Daraini; Yanti, Setianti; Warta, Waska (Finansha: Journal of Sharia Financial Management, 2025)
The increasing public awareness and concern about environmental issues has shifted the tendency of consumers to choose a product more selectively, the rise in environmental concerns has also led to emergence of green branding concept. The research used bibliometric analysis  of the scholarly discourse surrounding green branding from the years 2010 to 2024, utilizing the Scopus database to examinate the large data about various papers included in this study. Biblioshiny and VOSviewer software were used to analyse keyword co-occurrence and co-authorship in this topic. The result showing that the largest number of papers on green branding appeared in 2024, indicating there’s a growing academic interest in green branding topic. This study contributes to enhancing direction for researchers to examine the topic of green branding by offering the details of the journals information, authors, and countries that hold significant role in the green branding study alongside the terminology that frequently employed in green branding studies